Moderate soil compaction: Implications on growth and architecture in seedlings of 17 woody plant species - Alameda, David; Villar, Rafael (Soil and Tillage Research, 2009)
Generally, soil compaction is a stress factor affecting negatively the plant growth, but its effects vary between species and with the soil compaction range. The objective of this study is to know the different growth responses of 17 woody species subjected to moderate soil compaction, because most of the studies about this subject compare the effects in treatments with a wide and discrete compaction range. We explore the effects of moderate soil compaction on a continuous scale (0.1–1.0 MPa) on seedling growth. Seedlings of 17 woody species (deciduous and evergreens) mainly from Mediterranean ecosystems were grown in near optimal conditions (light, temperature and water) in a greenhouse with a sandy substrate. In general, there was a great variability of the responses depending on the species and the studied variable. About 53% of the species showed a higher total biomass with a moderate increase in soil compaction possibly being due to a greater root–soil contact. In the same way, 41% of species increase the relative growth rate and 35% the total area. Nevertheless, in spite of these positive effects on growth, for some species (23%) there was a decrease in the root proportion with soil resistance, as result of soil strength. These effects of moderate soil compaction could sum up in two general responses of woody plants: growth increment and architecture distortion. This might be relevant as a lower root investment may be a disadvantage under drought conditions. Finally, a simple conceptual model is proposed to understand the general effects of soil compaction on growth and biomass allocation
Keywords: biomass allocation; Mediterranean ecosystem; Penetration resistance; Relative growth rate

Moderate soil compaction: Implications on growth and architecture in seedlings of 17 woody plant species - Alameda, David; Villar, Rafael (Soil and Tillage Research, 2009)
Generally, soil compaction is a stress factor affecting negatively the plant growth, but its effects vary between species and with the soil compaction range. The objective of this study is to know the different growth responses of 17 woody species subjected to moderate soil compaction, because most of the studies about this subject compare the effects in treatments with a wide and discrete compaction range. We explore the effects of moderate soil compaction on a continuous scale (0.1–1.0 MPa) on seedling growth. Seedlings of 17 woody species (deciduous and evergreens) mainly from Mediterranean ecosystems were grown in near optimal conditions (light, temperature and water) in a greenhouse with a sandy substrate. In general, there was a great variability of the responses depending on the species and the studied variable. About 53% of the species showed a higher total biomass with a moderate increase in soil compaction possibly being due to a greater root–soil contact. In the same way, 41% of species increase the relative growth rate and 35% the total area. Nevertheless, in spite of these positive effects on growth, for some species (23%) there was a decrease in the root proportion with soil resistance, as result of soil strength. These effects of moderate soil compaction could sum up in two general responses of woody plants: growth increment and architecture distortion. This might be relevant as a lower root investment may be a disadvantage under drought conditions. Finally, a simple conceptual model is proposed to understand the general effects of soil compaction on growth and biomass allocation
Keywords: biomass allocation; Mediterranean ecosystem; Penetration resistance; Relative growth rate

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Herbivory in a Mediterranean forest: browsing impact and plant compensation - Focardi, Stefano; Tinelli, Aleandro (Acta Oecologica, 2005)
The compensatory response of plants to defoliation is likely to have important effects on plant–ungulate equilibria in forested ecosystems. We investigated the responses of six species of Mediterranean bushes to defoliation by wild ungulates, comparing an index of browsing impact with the productivity of plants in both open and exclusion plots. The data revealed a great diversity of plant responses to herbivory: Rubus ulmifolius was able to over-compensate and replace the lost tissues. Phillyrea latifolia exhibited a similar, albeit less evident, pattern, while Cistus salvifolius was severely damaged by browsing. Other species, such as Quercus ilex, Juncus acutus and Erica arborea, were not attacked to a large extent and suffered little or no harm. The results strongly suggest that Mediterranean ecosystems may tolerate large stocking rates of ungulates. However, the reduction of plant biomass due to browsing was very different in the six studied species, suggesting that when herbivory becomes severe the structure of the ecosystem will change with the more tolerant plants becoming more abundant. We can apply these results to improve management and conservation of relict coastal forests in the Mediterranean basin which are usually of small size and where decision-makers have to compromise between the conservation of plants and that of large mammals.
Keywords: Browsing; mediterranean environment; plant compensation; Relative growth rate; ungulates

Herbivory in a Mediterranean forest: browsing impact and plant compensation - Focardi, Stefano; Tinelli, Aleandro (Acta Oecologica, 2005)
The compensatory response of plants to defoliation is likely to have important effects on plant–ungulate equilibria in forested ecosystems. We investigated the responses of six species of Mediterranean bushes to defoliation by wild ungulates, comparing an index of browsing impact with the productivity of plants in both open and exclusion plots. The data revealed a great diversity of plant responses to herbivory: Rubus ulmifolius was able to over-compensate and replace the lost tissues. Phillyrea latifolia exhibited a similar, albeit less evident, pattern, while Cistus salvifolius was severely damaged by browsing. Other species, such as Quercus ilex, Juncus acutus and Erica arborea, were not attacked to a large extent and suffered little or no harm. The results strongly suggest that Mediterranean ecosystems may tolerate large stocking rates of ungulates. However, the reduction of plant biomass due to browsing was very different in the six studied species, suggesting that when herbivory becomes severe the structure of the ecosystem will change with the more tolerant plants becoming more abundant. We can apply these results to improve management and conservation of relict coastal forests in the Mediterranean basin which are usually of small size and where decision-makers have to compromise between the conservation of plants and that of large mammals.
Keywords: Browsing; mediterranean environment; plant compensation; Relative growth rate; ungulates

Growth response to ozone of annual species from Mediterranean pastures. - Gimeno, B S; Bermejo, V; Sanz, J; de la Torre, D; Elvira, S (Environmental pollution (Barking, Essex : 1987), 2004)
Ozone (O3) phytotoxicity has been reported on a wide range of plant species. However, scarce information has been provided regarding the sensitivity of semi-natural grassland species, especially those from dehesa Mediterranean grasslands, in spite of their great biological diversity and the high O3 levels recorded in the region. A screening study was carried out in open-top chambers (OTCs) to assess the O3-sensitivity of representative therophytes of these ecosystems based on the response of selected growth-related parameters. Three O3 treatments and 3 OTCs per treatment were used. Legume species were very sensitive to O3, because 78% of the tested species showed detrimental effects on their total biomass relative growth rate (RGR) following their exposure to O3. The Trifolium genus was particularly sensitive showing O3-induced adverse effects on most of the assessed parameters. Gramineae plants were less sensitive than Leguminosae species because detrimental effects on total biomass RGR were only observed in 14% of the assessed species. No relationship was found between relative growth rates when growing in clean air and O3 susceptibility. The implications of these effects on the performance of dehesa acidic grasslands and on the definition of ozone critical levels for the protection of semi-natural vegetation are discussed.
Keywords: Critical levels; Dehesa; Relative growth rate; Screening; Therophytes

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M F; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M. F.; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Root respiration, growth and nitrogen uptake of Quercus suber seedlings - Mata, C; Scheurwater, I; MartinsLoucao, M A; Lambers, H (PLANT PHYSIOLOGY AND BIOCHEMISTRY, 1996)
We tested the influence of two N-sources, NO3- and NH4+, on root growth and respiration of Quercus suber L. Seedlings were grown on hydroponics with 0.5 mM N as NO3- or NH4+ in a growth chamber. Root relative growth rate (RGR) of NO3--fed seedlings ranged from 9 to 34 mg g(-1) day(-1). These values are lower than those described for slow-growing herbaceous and for most woody species. Root respiration and the activity and capacity of the alternative pathway (AP) showed no differences between the two N-sources. Both activity and capacity of the AP were very low and the cytochrome pathway was fully engaged. Specific respiratory costs were calculated for maintenance, 6.3 nmol O-2 g(-1) s(-1), for nitrate uptake, 0.99 mol O-2 mol N-1, and for growth 5.4 mmol O-2 g(-1). These values are similar to those found for slow-growing herbaceous species. The major part of total root respiration, over 64%, was used for maintenance processes, and a much smaller fraction for growth and nitrate uptake.
Keywords: NH4+; NO3-; Relative growth rate; root respiration